5% Lidocaine Hydrochloride Cream for Wound Pain Relief: A Multicentre Observational Study. Issue 1 (2nd January 2022) - Janowska, Agata; Papa, Giovanni; Romanelli, Marco; Davini, Giulia; Oranges, Teresa; Stocco, Chiara; Arnez, Zoran Marji; Dini, Valentina
Abstract: Background: Lidocaine hydrochloride is frequently used for management of painful wounds. This prospective, multicentre study examined the effects of 5% lidocaine cream on wound pain relief. Material and methods: The study included 78 patients with painful wounds treated with 5% Lidocaine cream for two weeks in two Italian Hospitals. Patients' perception of pain was recorded by, using the 5-point Visual Rate Scale and the 11-point Numerical Pain Rating Scale. All medications and adverse events were evaluated in a daily diary. The primary outcome of the study was establishing the wound pain relief based on the results of 5-VRS and pain intensity based on the 11-NPRS testing from baseline to the end of treatment. Clinical aspects and adverse events were also collected. Results: Seventy-eight patients had a median age of 67.5 years (range 18-96 years). 62.8% were women. The wounds included traumatic wounds (n = 39), venous ulcers (n = 25), post-surgical wounds (n = 6) pyoderma gangrenosum (n = 6), vasculitis (n = 1) and pressure ulcer (n = 1). The intensity of pain significantly decreased from the baseline level established at the beginning of treatment (mean score 6.7 − 1.90) - to the level at end of treatment (3.0 − 2.23-; p < 0.0001). 9 patients prematurely stopped the treatment for healing (n = 4), wound improvement (n = 2) and adverse events related to the treatment. (n = 3). 13 patients presented a total of 25 adverse events, 4 of them were related to the treatment. Conclusion: The treatment of painful wounds with 5% Lidocaine Cream for 14 days resulted in reduced pain intensity, and showed high safety and tolerability.